Evaluation of Case detection rates of Pulmonary Tuberculosis before and after adoption of GeneXpert MTB/RIF - Mohammed, Suhad Hadi; Ahmed, Mohanad Mohsin; Al Mousawi, Ali Mahdi (Iraqi Journal of Science, 2018)
Cities witnessing mass-gathering events, such as Kerbala-Iraq, are peculiar in respect to their needs in controlling tuberculosis. DOTS was implemented in Kerbala almost two decades ago. GeneXpert MTB/RIF assay is adopted in the hope to escalate case detection rates, however, its performance is not evaluated yet. Records of 3254 patients suspected to have pulmonary TB whom they referred to the chest and Respiratory illnesses center of Kerbala governorate were analyzed. The overall trends of TB detection rates showed declining pattern over the year before the adoption of GeneXpert MTB/RIF. In the year of adoption of Xpert MTB/RIF, the detection rates raised, then after declined again. The GeneXpert MTB/RIF has added 17.7% increase in detectionrates.In conclusion: GeneXpertMTP/RIF usage had strengthen case detection rates especially for smear-negative cases.